ACTR-12. PRELIMINARY SAFETY AND EFFICACY OF A PHASE II TRIAL OF 18F-DOPA PET-GUIDED, DOSE-ESCALATED RADIOTHERAPY IN THE TREATMENT OF GLIOBLASTOMA. (5th November 2018) - Laack, Nadia; Pafundi, Deanna; Anderson, S; Hunt, Christopher; Zakhary, Mark; Kaufmann, Timothy; Wan Chan Tseung, Hok Seum; Lowe, Val; Yan, Elizabeth; Kizilbash, Sani; Uhm, Joon; Hu, Leland; et al.
Abstract: BACKGROUND: 18F-DOPA-PET thresholds reliably delineate areas of high-grade astrocytoma not otherwise recognized with standard MRI and may more accurately identify regions of aggressive, high-density disease. Herein we report the preliminary safety and feasibility data from an ongoing phase II study (MC1374; R01CA178200) evaluating 18F-DOPA-PET guided-dose-escalated radiotherapy for glioblastoma. METHODS: Newly diagnosed glioblastoma patients without contra-indications to 18F-DOPA-PET are eligible for study enrollment. Target volumes include: CTV51Gy=T1-gadolinium contrast-enhancing (T1-CE) disease, T2 FLAIR signal abnormality, and low-grade 18F-DOPA-PET uptake, +1cm; CTV60Gy=T1-CE and high-grade 18F-DOPA-PET uptake, +1cm; and CTV76Gy=T1-CE and high-grade 18F-DOPA-PET disease without expansion all given in 30 fractions simultaneously. Patients are followed with 18F-DOPA-PET in addition to standard clinical follow-up. Safety stopping rule specifies that after 10 or more patients have been enrolled, if more than 10% experience any of the following adverse events considered to be at least possibly related to treatment, enrollment will be suspended: Grade 3 or 4 irreversible CNS toxicity, Grade 4 non-hematologic, non-CNS toxicity, any Grade 5 toxicity. Futility analysis (and primary study aim) is powered to consider a success to be an MGMT-unmethylated patient who is without progression within 6 months from the time of craniotomy. If 16 or more successes are observed in the first 25 evaluable patients study will continue. RESULTS: 77 patients have been accrued since December 2013 with 68 evaluable for toxicity. Grade 3 CNS necrosis was noted in 3 (4.4%) patients; 2 additional patients developed symptoms that resolved in the subsequent cycle so did not count towards stopping rule. Other grade 3+ toxicities include: 1 patient with pre-existing vision dysfunction had Grade 4 optic nerve dysfunction; 2 Grade 4 hematologic events and 1 Grade 5 event(sepsis) due to temozolamide-induced cytopenias. CONCLUSION: 18F-DOPA-PET -guided dose escalation appears reasonably safe and tolerable in patients with high-grade glioma.